Magnification effect on fine motor skills of dental students - Wajngarten, Danielle [UNESP]; Pazos, Júlia Margato [UNESP]; Menegazzo, Vinícius Perassoli [UNESP]; Novo, Juliana Pimentel Duarte [UNESP]; Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (Public Library of Science (PLoS), 2021)
Objectives This study observed the effect of different magnification systems on dental students' real and perceived fine motor skills. Methods This was a laboratory-based experimental study. Students in the fifth year of an undergraduate dentistry program (N = 92) participated in this study. The dependent variables were real motor skills, perceived motor skills and time required to complete the fine motor skills test. The independent variable was the use of a magnification system under four conditions. For each condition, the Dental Manual Dexterity Assessment was performed, which consisted of inserting the #3195FF bur into targets positioned on a Styrofoam plate. The accuracy of each penetration of the targets was scored, using a point system with a maximum possible score of 246 points. Students' perceived fine motor skills were assessed using a visual analog scale (VAS) that ranged from zero for no skills to ten for maximum skills. A descriptive statistical analysis and the repeated measures ANOVA were performed (α = 0.05). Results The Galilean and Keplerian loupes were found to positively affect students' real fine motor skills (p<0.01); however, perceived fine motor skills and time were significantly better (p<0.01) under the naked eye. Conclusions Dental students' real fine motor skills were better when Galilean and Keplerian loupes were used, but the perceived fine motor skills were not.